Harassment of Female Students of Secondary Schools in Kashmir: A Study of District Shopian and Srinagar - Naz, Seema; Hamid, Aafiya (International Journal of Psychosocial Rehabilitation, 2020)
The study was conducted on the harassment of female secondary students. The sample of 80 female students from secondary schools from district Srinagar and district Shopian (40 from each district) was selected using random sampling. The investigator used a self-constructed questionnaire of 30 items to collect data from the subjects. The data collected was analysed through percentage statistics. During this study, it was found that students were not familiar with any anti-harassment policy of the government. Students even did not share problems of harassment with their family members, friends, or teachers. There was not any group or harassment cell in various institutions. Most of the female pupils revealed that there was not any counselor in their school. Students who wish for self-defense classes for females must be part of the school curriculum. The majority of female students believed there was a need to inform the female students about the various types of policies and agencies with whom they could register their grievances.